Value and risk effects of financial derivatives: Evidence of corporate governance on hedging, speculation and selective hedging strategies - Tashfeen, Rubeena (Victoria University of Wellington, 2016)
This study investigates whether there is a relationship between corporate governance and derivatives, whether corporate governance influence in firms impacts the association between derivatives and firm value, and whether corporate governance influence affects the association between derivatives and cash flow volatility, stock return volatility and market risk. This study uses two different data samples of publicly traded firms listed on the New York Stock Exchange. The first sample comprises a panel of 6900 firm year observations and the other consists of a panel of 6234 firm year observations both over the eight-year period from 2004-2011. With regard to whether there is a relationship between corporate governance and derivatives, the findings from the empirical results show that corporate governance does influence derivatives and therefore is an important determinant in the firm’s decisions to use derivatives. Of the thirteen corporate governance variables examined, board size, institutional shareholders, CEO age, CEO bonus, CEO salary, insider shareholders and total CEO compensation show significant association with derivatives. This study finds that derivative users exhibit higher firm value on account of the corporate governance influence, which is correspondingly largely insignificant for derivative non-users. Further the research indicates that the impact of corporate governance varies according to the different types of risks examined. Generally, the board of directors and CEO governance mechanisms reduce stock return volatility to achieve hedging effectiveness. This supports the view that directors and management take actions to reduce stock return volatility to protect their personal portfolios without having to bear the costs of hedging themselves. With respect to cash flow volatility, the board of directors and CEO related corporate governance mechanisms largely exhibit increased risk to show evidence of speculative behavior. It supports the perceptions that managers and directors have a strong motivation to show higher earnings to protect jobs and reputation and to enhance compensation. All the shareholder governance mechanisms encourage risk taking with respect to stock return volatility, without any increase in firm value. This is in line with research findings of market granularity by institutional and other larger block holders to indicate that these investors increase stock price volatilities and play the markets for their own financial gain. Besides they have little interest in diversifying firm risk as they already have well protected portfolios and would not want to incur additional costs of hedging. The study finds evidence of association between corporate governance and hedging, speculation and selective hedging. Of the thirteen corporate governance variables examined in the study board diversity consistently shows hedging effectiveness, with accompanying increase in firm value. While board meetings, institutional shareholders, block shareholders, CEO age, CEO base salary and CEO compensation exhibit exclusive speculative behavior. The remaining corporate governance mechanisms: board size, insider shareholding, CEO tenure, CEO bonus and audit committee size, show evidence of selective hedging behavior. The concurrent hedging and speculative behavior evidenced in this study supports literature in respect of selective hedging by non-financial firms. It also validates the idea that corporate governance delves in risk allocation strategies that have been evidenced by past research. The results remain unchanged, after using alternative measures for firm value and firm risk, and alternative methods of analyses.